Index depressive episode and antidepressant exposure were associated with illness characteristics of pediatric bipolar disorder - Inal, Neslihan; Ermis, Cagatay; Koc, Dogukan; Aksoy, Sena; Karacetin, Gul; Tuncturk, Mustafa; Diler, Rasim Somer (Wiley, 2022)
Objective Pediatric bipolar disorder (PBD) is a serious, recurrent disorder leading to severe functional impairment. As a first mood episode, index episode could affect the long-term course of the illness. This study aimed to investigate the clinical characteristics of youth with PBD from our multicenter, nationwide, naturalistic follow-up samples and to identify (i) the effects of index mood episode and (ii) the effect of previous antidepressant treatments on the age at mania onset of PBD. Method The study sample consisted of 271 youth with BD-I followed by the child and adolescent psychiatry clinics of seven different university hospitals and three research state hospitals, representing six geographic regions across Turkey. All diagnoses were made according to structured interviews, and all data were retrospectively obtained from clinical records by the clinicians. Results When patients with index depressive/mixed episodes (IDE, n=129) and patients with index (hypo)manic episodes (IME, n=142) were compared, the total number of mood episodes and rapid cycling feature were significantly higher in the IDE group than in the IME group. The Cox regression analysis adjusted for sociodemographic and illness characteristics revealed female adolescents in the IDE group treated with antidepressants were more likely to have an earlier onset of mania (hazard ratio=2.03, 95% confidence interval=1.31-3.12, p=0.001). Conclusion This is the first large-scale nationwide follow-up study in Turkey that indicated prior antidepressant treatments were associated with an earlier onset of mania in youth, particularly in adolescent females. Larger prospective studies are needed to identify neurodevelopmental processes underlying PBD and initiate prevention approaches.
Keywords: affective episode; antidepressant drugs; bipolar disorder; early onset; mood disorders